Enzyme-inspired single-atom photocatalysis for oxygen reduction to hydrogen peroxide - Zdražil, Lukáš; Cadranel, Alejandro; Zoppellaro, Giorgio; Günay-Gürer, Ayse; Baďura, Zdeněk; Panáček, David; Kmentová, Hana; Otero, Camila; Kment, Štěpán; Huergo, Maria Ana; Fonda, Emiliano; Zbořil, Radek; et al. (Nature communications, 2025)
Photocatalysis presents a promising route for generating sustainable, high-energy-density fuels. However, conventional photocatalysts based on rigid binary metal compounds face significant limitations, including fixed band gaps, rapid charge recombination, and non-specific reaction pathways - ultimately leading to limited selectivity and yield. Critically, they lack the site-specific selectivity characteristic of enzymatic systems, a feature essential for achieving high efficiency, control, and precision. Inspired by cytochrome c oxidase, we report the development of Cu-single-atom-enhanced carbon dots as the enzymatic-like photocatalyst. By mimicking enzyme´s site-specific electron transfer cascade, these carbon dots enable the selective photocatalytic reduction of oxygen to hydrogen peroxide under ambient conditions. This study introduces a strategy for translating enzymatic precision into photocatalytic materials design, bridging molecular and materials catalysis for sustainable energy and chemical transformations.